Worst Case Pricing of Rainbow Options - Jürgen Topper (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2001)
Options on two underlyings are a common exotic product in the equity and FX derivatives market. The value of these kinds of options depends on the correlation of the two underlyings. We will present a model to compute a lower bound for the price of this option. The model, represented by a non-linear parabolic PDE, is implemented with finite elements in order to demonstrate the results with several derivatives from the European market.
Keywords: C63; G13; 330